2015
DOI: 10.1097/ta.0000000000000808
|View full text |Cite
|
Sign up to set email alerts
|

Nonoperative management of blunt liver and spleen injury in children

Abstract: Expert opinion, guideline, grades I to IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
107
1
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 140 publications
(120 citation statements)
references
References 72 publications
5
107
1
7
Order By: Relevance
“…Similar to what was previously reported in other series 1,3,6,7,15,23,27 , pedestrian-like traffic accidents are the predominant trauma mechanism in the hepatic and splenic injuries due to closed trauma in our study group, followed by falls from high heights in second place and others less common causes, as trauma on bicycle or skateboards, trauma with blunt objects among others. The most affected group was the 5 to 10 years old children.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…Similar to what was previously reported in other series 1,3,6,7,15,23,27 , pedestrian-like traffic accidents are the predominant trauma mechanism in the hepatic and splenic injuries due to closed trauma in our study group, followed by falls from high heights in second place and others less common causes, as trauma on bicycle or skateboards, trauma with blunt objects among others. The most affected group was the 5 to 10 years old children.…”
Section: Discussionsupporting
confidence: 77%
“…Multiple studies are in agreement with what is found in our series of patients, although most of these are focused on determining cut points to move from NOM to surgical management and not to establish factors that act as predictors of this outcome or to prevent the complications associated with the delay of these 6,7,23,27 . These findings may have a especial significance when using pediatric abdominal trauma algorithms 23 , since they allow us to anticipate the patient's clinical condition, in order to reduce the associated morbidity and mortality. The majority of algorithms used as a cutoff point for surgical intervention are a requirement for serial transfusions that exceed half of the blood volume, 40 cc/kg or 4 RBCU during the 24 hours after the injury.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations